PENGARUH PUTARAN SPINDEL, GERAK MAKAN DAN KEDALAMAN POTONG TERHADAP GETARAN SPINDLE HEAD HASIL PROSES DRILLING - Yuni Hermawan (ROTOR, 2012)
The process  of  drilling  or  often  referred  to  as  the  drill  is  the  simplest machining  process  among  other  machining  processes.  Usually  in  the  garage  or workshop process is called the drill, although this term is actually less accurate. The process of the drill is intended as a process of making a round hole by using a drill (twist drill). While the process of drilling is the process to expand / enlarge the hole that can be done with a drill rod is not only done on the drill machine, but it could also machine tool, machine freis, or drilling machines. From the research results can be seen the effect of the parameters used to the chatter values obtained chisel. Can be seen carving the smallest value of the vibration generated from experimental data 1 is =0.6361 m/s2 at n = 136 rpm, f = 0,07 and a = 14 mm. While the biggest chisel vibration acceleration values obtained from experimental data collection to 27 for =,4267 m/s2 at n = 681 rpm, f = 0,22 and a = 20 mm. From the regression equation can be known parameters of the most influential pieces of depth of cut. The results in general that the value of vibration acceleration and determination, after  the meal motion raised the value of vibration acceleration chisel and roundness are also growing, this was due to the greater movement of food is used then the resulting anger is also getting thicker  so that the required cutting force increasing large. Consequently tangential force is also rising and  causing the radial force and moment coupling. Moments and radial forces which cause bending and twisting of the chisel, consequently the greater the roundness deviation. Key words: drilling, feeding, dept of cut, spindle head and vibration.